Ankle Joint Distraction in Traumatic Injuries: Step-by-Step Operative Approach - Beth Lineham; Hemant Sharma (Journal of Foot and Ankle Surgery (Asia Pacific))
Ankle joint distraction (AJD) has gained increasing recognition as a joint-preserving strategy in the management of complex posttraumatic ankle injuries, particularly in younger, active patients where traditional salvage procedures may compromise long-term function. This invited article presents a detailed surgical technique for AJD utilizing a circular external fixator system. Indications include posttraumatic osteoarthritis, talar chondral lesions, and residual joint incongruity following intra-articular fractures. The technique involves meticulous preoperative planning, precise application of the external fixator, and gradual joint distraction. Intraoperative considerations, distraction protocols, and postoperative rehabilitation strategies are described to guide optimal outcomes. Pearls and common pitfalls are discussed, emphasizing the importance of patient selection and multidisciplinary care. AJD offers a promising approach for biologic joint preservation in a select trauma population. This article aims to provide a comprehensive, step-by-step guide, from preoperative planning to postoperative care, to support the successful implementation of this procedure.